Future of sports marketing: trends, challenges, solutions - Moore, Gareth (Henry Stewart Talks, 2008)
New areas of development in sport marketing, What can sponsors, clubs, teams or events do to keep up with the changes and get the best out of them?, What technology, methodologies and tools will get the best results
Archived at 2022/04/04